Association of serum total IgE and allergen-specific IgE with insulin resistance in adolescents: an analysis of the NHANES database - Yaping Liu; Xiaoxia Wang; Yong Liu (BMC Pediatrics, 2024)
Abstract Background Recent studies have found that total immunoglobulin E (IgE) and allergen-specific IgE were associated with some metabolic diseases. However, the role of IgE in metabolism among adolescents is still unclear. Herein, this study aims to investigate the associations of serum total IgE and allergen-specific IgE with insulin resistance (IR) in adolescents, in order to provide some reference for the prevention and treatment of metabolic diseases in a young age. Methods Data of 870 adolescents were extracted from the National Health and Nutrition Examination Survey (NHANES) database in 2005–2006 in this cross-sectional study. Weighted univariate and multivariate logistic regression analyses were utilized to screen covariates and explore the relationships of serum total IgE and allergen-specific IgE with IR. The evaluation indexes were odds ratios (ORs) and 95% confidence intervals (CIs). In addition, these relationships were also assessed in subgroups of allergy history, asthma history, and number of allergens. Results Among eligible adolescents, 168 had IR. No significant association between serum total IgE level and IR was found. However, adolescents with higher level of allergen-specific IgE to rye grass [OR = 0.47, 95%CI: (0.25–0.91)], white oak [OR = 0.57, 95%CI: (0.37–0.88)], or peanut [OR = 0.38, 95%CI: (0.15–0.97)] seemed to have lower odds of IR, whereas those had higher level of shrimp-specific IgE [OR = 2.65, 95%CI: (1.21–5.84)] have increased odds of IR. In addition, these associations between allergen-specific IgE and IR were also discovered in adolescents who had allergy history or asthma history, or had different numbers of allergens. Conclusion Paying attention to different allergens in adolescents may be important in the early identification of IR among this high-risk population. The study results relatively provided some reference for further exploration on IR prevention.